2020
DOI: 10.3390/cells9122674
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Analgesic Effect of Intrathecal Applications of Neuroactive Steroids in a Rodent Model of Post-Surgical Pain: Evidence for the Role of T-Type Calcium Channels

Abstract: Preemptive management of post-incisional pain remains challenging. Here, we examined the role of preemptive use of neuroactive steroids with activity on low-voltage activated T-type Ca2+ channels (T-channels) and γ-aminobutyric acid A (GABAA) receptors in the development and maintenance of post-incisional pain. We use neuroactive steroids with distinct effects on GABAA receptors and/or T-channels: Alphaxalone (combined GABAergic agent and T-channel inhibitor), ECN (T-channel inhibitor), CDNC24 (GABAergic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…were compared to the vehicle administration. In animals that underwent skin incision, we focused on mechanical hyper-analgesic effects as an important feature of incisional pain for two main reasons: it is very commonly observed in a clinical setting of incisional pain [16,22,23] and, as published previously, it is sensitive to pharmacological and biochemical modulation [16,17]. The paw withdrawal responses (PWR) were determined in the incised (hyper analgesic effect) right hind paw (Figure 1 left side) and non-operated (left) paws (Figure 1 right panels).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…were compared to the vehicle administration. In animals that underwent skin incision, we focused on mechanical hyper-analgesic effects as an important feature of incisional pain for two main reasons: it is very commonly observed in a clinical setting of incisional pain [16,22,23] and, as published previously, it is sensitive to pharmacological and biochemical modulation [16,17]. The paw withdrawal responses (PWR) were determined in the incised (hyper analgesic effect) right hind paw (Figure 1 left side) and non-operated (left) paws (Figure 1 right panels).…”
Section: Resultsmentioning
confidence: 99%
“…(2) the majority of current pain studies in animals are performed using males [15]. Thus, we believe that the research focus should also be on female pain perception [13,16]. Incision pain model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both alphaxalone and ALLO are well known as positive allosteric modulators of GABA A receptors, we have previously reported that both of these agents are also fairly potent blockers of neuronal Ca V 3.2 isoform of T-channels in sensory neurons [40], and display prominent analgesia in vivo [41]. Over the last decade, our group has extensively studied T-channel blocking properties and analgesic potential of neurosteroids [42,43,44 && ], particularly a novel synthetic 5b-reduced neurosteroid analogue, 3b-OH ((3b,5b,17b)- ] that is at least partly mediated by the inhibition of Ca V 3.1 isoform of T-channels. Specifically, we found that hypnotic effect of 3b-OH was greatly diminished in the global Ca V 3.1 knock-out (KO) mice when compared to their wild-type littermates [46 && ].…”
Section: Neurosteroids In Anesthesia and Analgesiamentioning
confidence: 99%